When reborn as a Phoenix is possible: The Plebiscite-Nobel case of Juan Manuel Santos Calderón - Arredondo Espinosa, Alexis (Estudios sobre el Mensaje Periodístico, 2018)
The Colombian peace process between the government of Juan Manuel Santos Calderón and the guerrilla of FARC, depends on a last step for its approval: a plebiscite. Nevertheless, the victory of No in the polls, unties an uncertainty that surrounds the future of the process. Only a fact of great international support could save the agreement rejected by the Colombian people, something big, a Nobel. The purpose of this work is to know, through a quantitative content analysis, the information treatment from the plebiscite on the peace agreements in Colombia, until the day that Juan Manuel Santos wins the Nobel Peace Prize. The results are focused on the identification of the main actors, the most relevant themes and the relationship of the events around the Nobel and the peace plebiscite, with the positive and negative image of the agreements.
Keywords: Juan Manuel Santos; FARC; Colombian conflict; Colombian peace process; Colombian peace agreement referendum.